Mycorrhizal synthesis between Pisolithus arhizus and adult clones of Arbutus unedo in vitro and in nursery - Gomes, Filomena (2013)
Arbutoid mycorrhizae were synthesized between adult selected clones of Arbutus unedo L. and Pisolithus arhizus. Two micropropagated clones were tested: AL1, in vitro and C1 (acclimatized plants) in nursery and later in a field trial. In vitro, rooted shoots were transferred to test tubes containing the substrate previously inoculated with mycelium cultured on agar. In the nursery, two inoculation treatments were tested (vegetative inocula or dry sporocarps) and compared to control plants. In the field trial, plants from nursery inoculation treatments were compared and an additional control treatment using seedlings was implemented. Plant height was evaluated 4 months later in the nursery and 20 months later in the field trial. Roots were examined by morphological and histological studies: a) in vitro plantlets one month after inoculation and nine months after acclimatization; and b) 20 months after the field trial was established. Arbutoid mycorrhizae were observed in vitro one month after inoculation, indicating compatibility between A. unedo and P. arhizus. These showed the presence of a mantle, Hartig net, and intracellular hyphal complexes confined to the epidermal root cells. Arbutoid mycorrhizae were also observed nine months after acclimatiza- Fund project: This work was supported by a PhD fellowship (SFRH/BD/37170/2007) from the Portuguese Foundation for Science and Technology (FCT) The online version is available at http://link.springer.com Filomena Gomes ( ) • Esteban San Martin Filomena Gomes. CERNAS, Dep. Recursos Florestais, Escola Superior Agrária Coimbra, Bencanta, 3040-316, Coimbra, Portugal, Tel: 351 239 802940, Fax: 351 239 802979, Email: fgomes@esac.pt Helena Machado INIAV, Instituto Nacional de Investigação Agrária e Veterinária, IP., Av. República, Quinta do Marquês 2780-159 Oeiras, Portugal A. Portugal • Jorge M. Canhoto Centre of Functional Ecology, Department of Life Sciences, University of Coimbra, Ap. 3046, 3001-401 Coimbra, Portugal. Corresponding editor: Chai Ruihai tion in inoculated and control plants. In order to confirm the identity of mycorrhizae, molecular techniques were used, in previously inoculated in vitro plants, 12 months after acclimatization. Thelephora and Hebeloma mycorrhizae, two types of highly competitive and widespread mycorrhizae on nurseries were identified. In the nursery, dry sporocarp treatment improved plant height after four months. In a field trial (20 months later), plants growth did not show significant differences. By this time, mycorrhized roots with Cenococcum geophilum and other types were identified. These results and their implications on A. unedo breeding program are discussed.